Potential of Banana Stem as Bio-adsorbent for Palm Oil Mill Effluent (POME) Treatment: A Systematic Literature Review - Khamis, Muhammad Nur Hafizuddin; Jalil, Mas Rahayu (Progress in Engineering Application and Technology, 2021)
First Banana stem is an agricultural waste where abundance of unusable banana stem can be considered as increase in amount of waste. This research was aimed to investigate the potential of banana stem as bio-adsorbent in palm oil mill effluent (POME) treatment, in order address the increase amount of banana stem as agricultural waste. In this research, adsorbing capabilities of banana stem as bio-adsorbent and various data supporting the potential of banana stem were investigated based on previous literature and findings through systematic literature review (SLR) method. The banana stem adsorbing capabilities studied in this research were focussed on the removal of heavy metal, reduction of chemical oxygen demand, removal of suspended solid and turbidity. The data obtained shows that banana stem have the ability to adsorb heavy metal such as copper ion, zinc ion and iron ions which exist in palm oil mill effluent (POME). The data also shows that banana stem bio-adsorbent are capable of reducing chemical oxygen demand (COD) value of various wastewater up to more than 50% and are capable of reducing the amount of suspended solids and turbidity. Based on the results we can assumed that banana stem bio-adsorbent can be an alternative method in palm oil mill effluent (POME) treatment. However, further laboratory work should be done in the future to prove this claims.